Ahlquist, Irving (audio interview #3 of 5) - Ahlquist, Irving (b. 1916 - d. 2004); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This third of five interviews conducted in Ahlquist's office in the CSULB History Department. The audio quality of the interview is good. 3/17/1978